2013
DOI: 10.14233/ajchem.2013.13771
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from Arundina graminifolia and Their Anti-Tobacco Mosaic Virus Activities

Abstract: to Indonesia and across the Pacific Islands. The genus is considered to possess activities of detoxification, antiarthritis and abirritation and is used as antidote and demulcent 1. In recent years, several papers have described phytochemistry investigations of A. gramnifolia and was found to be rich in stilbenoids and triterpenes 2-5. Motivated by a search for bioactive compounds from this plant, further chemical investigation were carried out. As a result, a new phenolic compounds (1), together with three kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Arundina graminifolia (D. Don) Hochr., a species widely distributed in subtropical Asia and known as bai-yang-jie in Chinese, has a long history of use as one of the major drugs in a formula “BaoGan Capusle” with the efficacy of heat clearing and detoxifying, dispersing blood and relieving pain, reducing inflammation and promoting urination and so on [1]. Previous phytochemical investigation focusing on the chloroform and ethyl acetate exacts of A. graminifolia had resulted in the separation of stilbenoids [2,3,4], phenols [5,6,7], flavonoids [8,9] and other ketones [3,10,11]. However, the works on the polar parts of the plant are few.…”
Section: Introductionmentioning
confidence: 99%
“…Arundina graminifolia (D. Don) Hochr., a species widely distributed in subtropical Asia and known as bai-yang-jie in Chinese, has a long history of use as one of the major drugs in a formula “BaoGan Capusle” with the efficacy of heat clearing and detoxifying, dispersing blood and relieving pain, reducing inflammation and promoting urination and so on [1]. Previous phytochemical investigation focusing on the chloroform and ethyl acetate exacts of A. graminifolia had resulted in the separation of stilbenoids [2,3,4], phenols [5,6,7], flavonoids [8,9] and other ketones [3,10,11]. However, the works on the polar parts of the plant are few.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the structure of compound 1 was assigned as 3-hydroxy-1-(2-(2-hydroxy-4,6-dimethoxyphenyl) benzofuran-5-yl) propan-1-one and gives the trivial name of fargesilignan A. Many polyphenols are known to exhibit antitobacco mosaic virus activities [17][18][19] . Compounds 1-6 were therefore tested for antitobacco mosaic virus activities using the half-leaf method 20 .…”
Section: Resultsmentioning
confidence: 99%
“…This plant is considered to possess activities of detoxification, antiarthritis and abirritation and it is used as antidote and demulcent in traditional Chinese medicine 1 . The previous phytochemical researches on A. gramnifolia had revealed that stilbenoids [2][3][4] , sterols 5,6 , triterpenes 7,8 and phenols 5,9 are major components isolated from this plant.…”
Section: Introductionmentioning
confidence: 94%